Spiritual Journey In Paulo Coelho's Novel The Alchemist (1993): An Individual Psychology Approach - Nursecha, Nanang; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This research paper is aimed to show visible image of Paulo Coelho's novel which is analyzed by using individual psychology approach. The objectives of the research are to analyze the novel based on the structural elements and to analyze the novel based on individual psychology approach proposed by Alfred Adler. This research belongs to qualitative research. Data of the research are divided into two, primary data and secondary data. The primary data of the research is The Alchemist novel and secondary data of the research are biography of the author, websites, and other source about individual psychology approach that support the analysis. The method to analyze this data is descriptive analysis. The researcher comes to conclusion as follows. Based on individual psychology approach analysis, Paulo Coelho illustrated psychological phenomena in which an individual has experienced spiritual journey. The outcome of the study shows that Paulo Coelho illustrates psychological phenomenon that an individual experiences when he is travelling to get treasures. In the search for treasure, he finds something more important than the material that is high spiritual level.